Legal Policy to Handle Medicine Price in Indonesia: A Comparison Study With Other Countries - Zuardin, Zuardin; Ratodi, Muhamad (International Conference on Sustainable Health Promotion, 2018)
The use of medicinal right with an affordable price becomes a necessity for the public. The affordable medicine will reduce public health risks due to the public inability to buying common generic medication. An irrational difference in the medicine selling price at the consumer level was caused by a free price determined by pharmacy industries in the market mechanism. The medicine selling price policies for pharmacies were only accommodated through the Minister of Health Decree Number 720/Menkes/SKIX/2006 which in fact can not provide a solution. Therefore, the government has to control the selling price in the market mechanism and to seek the strong legal force.